Constrained non-linear optimisation of a process for liquefaction of natural gas including a geometrical and thermo-hydraulic model of a compact heat exchanger. (2nd February 2015) - Skaugen, G.; Hammer, M.; Wahl, P.E.; Wilhelmsen, Ø.
Highlights: Optimisation of a LNG-process including a full cryogenic heat exchanger model. The objective function is to minimise compression work. Size and weight of the heat exchanger are additional constraints in the optimisation. Results compared minimal internal approach temperature (MITA) – formulation. Discusses how low MITA value implicitly assumes unrealistic large heat exchangers. Abstract: A great deal of effort has been put into improving natural gas liquefaction processes, and a number of new process configurations have been described. Recent literature has identified a need for more realistic heat exchanger models to obtain optimum design and operating conditions that do not compromise safety, or that are unrealistic. Here we describe a concept for finding the design and operating conditions of a single mixed-refrigerant process which gives minimum power consumption under given space or weight constraints. We use a sophisticated heat exchanger modelling framework that takes into account system geometry and resolves the details of the heat exchanger through conservation equations coupled with accurate models of thermo-physical properties. First, we find the feasible region which does not compromise safety with Ledinegg instabilities. We then identify the optimal operating conditions for a specific design within this region, before identifying the process design that requires least power consumption. We illustrate how this differs from a purely thermodynamic optimisation, and discuss our key results.